Anti-inflammatory activity of Alpinia officinarum hance on rat colon inflammation and tissue damage in DSS induced acute and chronic colitis models - Vijayabharathi Rajendiran; Vidhya Natarajan; Sivasithamparam Niranjali Devaraj (Food Science and Human Wellness)
The purpose of this study was to investigate the possible prophylactic effects of Alpinia officinarum hance on experimentally induced acute and chronic colitis models, in-vivo and in-vitro. Acute and chronic colitis were induced in Male Wistar rats by administration of Dextran Sulfate Sodium (DSS) in drinking water. DSS induction exhibited colon shrinkage, increased the Disease Activity Index (DAI) score, increased the levels of inflammatory markers and caused severe anemia. DSS induced animals, co-treated with the hexane extract of Alpinia officinarum (HEAO) (200 mg/kg body wt), effectively suppressed colonic injury that was evidenced by the reduced DAI score, colon weight/length ratio, histological damage, proinflammatory markers and MPO activity. Further, it restored the colonic antioxidants near to normal levels by regulating the oxidative stress via attenuation of lipid peroxidation. Our results revealed that the degree of colitis caused by the administration of DSS was significantly attenuated by HEAO. In addition, the in-vitro study showed that HEAO treatment inhibited the proliferation of HT-29 cells and down regulated the mRNA expression of NF-κB and COX-2. Taken together, these results suggest that HEAO is a promising anti-oxidant and anti-inflammatory agent that support its possible therapeutic role in the treatment of colitis. Keywords: Alpinia officinarum, Antioxidants, Inflammation, Dextran sulfate sodium (DSS), Inflammatory bowel diseases (IBD)